Managing Sovereign Debt and Debt Markets through a Crisis : Practical Insights and Policy Lessons. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The crisis highlighted the importance of debt management in containing debt-related risks and the associated impact on debt markets. The impact of the crisis on debt levels, and the consequent implications for fiscal consolidation, has been the subject of much discussion and analysis. However, there has been relatively less focus on the issue of how that debt should be managed, including how its composition should be structured so as to mitigate key risk exposures, and its implications for debt market functioning. That task proved significantly complex and challenging through the crisis, particularly in advanced economies, with additional dimensions of risk revealed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet